The Population Aging – A Factor of Increasing the Needs for Long-Term Care for the Person - Pandurska, Ralitza (Research Papers, 2019)
The social systems of the countries, especially pension and health, have a strong impact on demographic transformations. This requires their adaptation to the changing demographic and socio-economic environment. The present study aims tо highlighting the problems related to the growing needs of a long-term care for the elderly people in Bulgaria and their increasing dependence on relatives and the care of the institutions.In order to achieve this goal, several more important tasks related to the analysis of the demographic indicators determining the aging of the population in Bulgaria are set; tracking the interrelationship between the growth of middle age and the population aging and increasing the need for long-term care for individuals; focusing on the main moments of the National Long-term Care Strategy in Bulgaria, making some recommendations for improving the quality of long-term care in the country.Analytical, comparative, inductive and deductive methods have been used.As a result of the research and analysis of the demographic processes and factors determining the aging of the population in Bulgaria, the indisputable necessity of long-term care for the elderly has been proved. On this basis are presented the main measures that need to be taken to overcome the reliance of older people and to promote their qualitative life.
Keywords: Demographic changes; Population aging; Social systems; Long-term care